2003
DOI: 10.1124/jpet.103.060301
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Olfactory Mucosa-SpecificCyp2g1Gene: Impact on Acetaminophen Toxicity in the Lateral Nasal Gland, and Tissue-Selective Effects onCyp2a5Expression

Abstract: CYP2G1 is a cytochrome P450 monooxygenase expressed uniquely in the olfactory mucosa (OM). We have generated Cyp2g1-null mice to identify the roles of CYP2G1 in the biology and the tissue-specific toxicity of xenobiotic compounds in the nose. Homozygous Cyp2g1-null mice are viable and fertile; they show no evidence of embryonic lethality, morphological abnormality, or developmental deficits; and they seem to have normal olfactory ability. However, OM microsomes from Cyp2g1-null mice were found to have signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 30 publications
2
36
2
Order By: Relevance
“…For example, a reduction was seen in the expression of the Cyp2a5 gene in Cyp2g1 knockout animals (Zhuo et al, 2004), and bidirectional transcriptional activity of PGK-neo resulted in embryonic lethality in heterozygote multiple endocrine neoplasia type 1 chimeric knockout mice (Scacheri et al, 2001). Most often, the PGK-neo cassette was found to affect neighboring genes when inserted within gene clusters or locus control regions, such as the myogenic regulator factor genes (Olson et al, 1996), ␤-like globin locus control region , the Hox gene cluster (Ren et al, 2002), and the granzyme B gene cluster (Pham et al, 1996).…”
Section: Arylamine N-acetyltransferase Nat3(ϫ/ϫ) Knockout Micementioning
confidence: 99%
“…For example, a reduction was seen in the expression of the Cyp2a5 gene in Cyp2g1 knockout animals (Zhuo et al, 2004), and bidirectional transcriptional activity of PGK-neo resulted in embryonic lethality in heterozygote multiple endocrine neoplasia type 1 chimeric knockout mice (Scacheri et al, 2001). Most often, the PGK-neo cassette was found to affect neighboring genes when inserted within gene clusters or locus control regions, such as the myogenic regulator factor genes (Olson et al, 1996), ␤-like globin locus control region , the Hox gene cluster (Ren et al, 2002), and the granzyme B gene cluster (Pham et al, 1996).…”
Section: Arylamine N-acetyltransferase Nat3(ϫ/ϫ) Knockout Micementioning
confidence: 99%
“…In mice and several other mammalian species, CYP2G1 is uniquely expressed in OM, and mouse CYP2G1 has been found to be active toward both endogenous (e.g., testosterone) and exogenous substrates (e.g., the olfactory toxicant dichlobenil) (Hua et al, 1997;Gu et al, 1998Zhuo et al, 2004. However, humans no longer have a functional CYP2G gene (Sheng et al, 2000).…”
Section: Mousementioning
confidence: 99%
“…Testosterone is a known substrate for multiple P450 enzymes. The roles of CYP2A5/2G1 in testosterone hydroxylation in OM (Zhuo et al, 2004) and the role of CYP2A5 in testosterone hydroxylation in liver and lateral nasal gland have been studied previously using Cyp2a5-null and Cyp2g1-null mice, but the contributions of the CYP2A(4/5)BGS enzymes to testosterone metabolism in the lung and brain have not been examined until now. Our results showed that, in the lung, they play an important role in the formation of 15a-OH-T (the most abundant metabolite detected in lung), 15b-OH-T, 2b-OH-T [presumably all formed by CYP2A5 , and 16b-OH-T [presumably formed by CYP2B (Sonderfan et al, 1987)]; these enzymes do not appear to play a role, however, in the formation of 16a-OH-T [preferentially formed by CYP2D9 (Ichikawa et al, 1989)].…”
Section: Mousementioning
confidence: 99%
See 1 more Smart Citation
“…In mice, APAP causes toxicity in several organs, including the liver, kidney, lung, the nasal olfactory mucosa and respiratory mucosa, and the lateral nasal gland (LNG) (Zhuo et al, 2004;Gu et al, 2005). The LNG, found in most mammalian species, including humans, is one of the largest anterior nasal glands (Moe and Bojsen-Moller, 1971).…”
Section: Introductionmentioning
confidence: 99%